Improving Student Learning Outcomes with the Problem Based Learning Model: Classroom Action Research at the State Islamic Primary School - Yusnidar; Mauliana, Isna; Ulfa, Nadiya; Fitria, Ainal (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve student learning outcomes by using a problem based learning model. This research uses a type of classroom action research. The subjects of this research were third grade students of State Islamic Primary School of 41 Aceh Besar. Data collection techniques in this research are observation and tests. Data were analyzed using descriptive statistical techniques. The results of the research show that student learning outcomes in the third grade Theme 8 material at State Islamic primary School of 41 Aceh Besar using the problem based learning model have increased in each cycle. In cycle I, student learning outcomes reached 73.33% but had not yet reached the classical success indicators, then in cycle II student learning outcomes increased, namely reaching 80% but had reached the classical success indicators. These results show that by using a problem-based learning model, student learning outcomes have increased and achieved indicators of success. Therefore, the problem-based learning model can be used as an alternative learning model that can overcome the problem of low student learning outcomes.